Návrh robotického pracoviště pro lepení magnetů na DC motory - Kűhnel, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Předmětem diplomové práce je návrh obecné koncepce pracoviště pro lepení magnetů do DC statorů. Práce obsahuje výběr průmyslových robotů a jejich rozmístění, návrh koncových efektorů pro manipulaci se segmenty a statory, a návrh řešení konstrukčních uzlů v pracovišti. Mezi konstrukční uzly patří: karuselové stoly i s úchopovými systémy, otočné stoly na palety a manipulátory. Na závěr práce je vytvořený koncept řešení bezpečnosti pracoviště podle aktuálních bezpečnostních norem a platné legislativy.

The diploma thesis deals with the design of a general concept workplace for gluing magnets to the DC stators. The thesis is focused on the selection of industrial robots and their location, the design and the construction of end effectors for manipulation with segments and stators and the proposal of solution for engineering units on a workplace. Among the construction units belong: revolving tables with gripping systems, rotary tables on pallets and construction manipulators. At the end of the thesis the concept of the solution for workplace safety is created according to current legislation and safety standards.
Design of a Robotic Cell for Gluing of Magnets of DC Motors
Keywords: Robotické pracoviště; lepení magnetů; otočný stůl; manipulátor; Robotic workplace; gluing magnets; rotary table; manipulator